Are Jobs More Polarized in ICT Firms? - Petri Böckerman; Seppo Laaksonen; Jari Vainiomäki (Institute for the Study of Labor (IZA), 2016)
We perform decompositions and regression analyses that test the routinization hypothesis and implied job polarization at the firm level. Prior studies have focused on the aggregate, industry or local levels. Our results for the abstract and routine occupation groups are consistent with the routinization hypothesis at the firm level. The observed changes are linked to ICT adoption. Thus, disappearing middle-level (routine) work can be traced to firm-level technological change.
Keywords: J23; J24; J31; O33; 330; skill-biased technological change; job polarization; routinization